Strategic inter-cropping for saline agriculture: quantifying the impact of Medicago sativa–Festuca arundinacea ratios on soil properties and crop performance - Sun, Yuchen; Shi, Jiayu; Liu, Xindi; Zhao, Li; Yang, Guofeng; Tao, Qibo; Zhong, Shangzhi; Zhang, Qingping; Miao, Fuhong (Frontiers in Plant Science, 2025)
Soil salinization is an abiotic stress that hinders crop growth, agricultural productivity, and environmental protection. In this study, alfalfa (Medicago sativa) and tall fescue (Festuca arundinacea) were sown in seven inter-cropping ratios, with monocultures as controls to explore the effects of inter-cropping grasses on yield, water-soluble salt content, pH, and total nitrogen in saline-alkali land, and to establish whether inter-cropping can alleviate salinity and alkalinity. In addition, this study aimed to screen and identify the best alfalfa and tall fescue inter-cropping ratio. The results revealed that (1) Alfalfa and tall fescue had the best productivity and the highest crude protein content at an inter-cropping ratio of M6F4, M7F3, and M8F2, respectively. Besides, inter-cropping improved the land-use efficiency of saline land by altering the plant stem-leaf ratio to adapt to the resource competition. (2) Alfalfa and tall fescue inter-cropping at M3F7, M4F6, and M7F3 decreased the 21% soil salt and 7.8% pH and increased the 34.7% total nitrogen content. (3) Correlation analysis revealed significant correlations among soil salt content, pH, nitrogen, inter-cropping yield, stem-leaf ratio, and plant competition rate. These findings indicate that inter-cropping alfalfa and tall fescue in the ratio M6F4, M7F3, and M8F2 best improves the utilization efficiency of saline land.